Pricing under uncertainty: Forward and option pricing in sports markets - SAINAM, Preethika (Institutional Knowledge at Singapore Management University, 2022)
Tickets to popular elimination style tournaments (e.g., NFL Super Bowl) are expensive and scarce. Sports organizations sell these tickets well in advance of the final game. Fans hesitate to buy them because they are unsure about whether their favorite team will play in it. We present two alternatives to the current practice: consumer forwards and options. A fan pays a reserve price to secure her team-specific forward ticket. If that team makes it to the final game, the fan must (in the option case, has the choice to) pay an exercise price to purchase the ticket. If the team does not make it, the forward expires (the option does not). We demonstrate how such alternatives buffer consumers from uncertainty and enhance profits under uncertainty. In a market with heterogeneous fan types, we demarcate conditions under which these alternative pricing mechanisms yield higher profits than advance pricing, including under capacity constraints.